Malaysia taxation-questions manual - Zainal Abidin , Nor Hafizah; Mohd Isa, Khadijah (s.n, 2013)
Malaysia taxation is a compulsory course in all accountancy undergraduate programmes and professional courses. The course aims to provide a good foundation on the fundamental of taxation through understanding the core area of the Malaysia taxation system. Upon completion of the course, students should be able to apprehend the taxation system. Upon completion of the course, students should be able to apprehend the tax administration matters and to prepare tax computation for individual and corporate tax payers based on the relevant tax laws and regulations. Hence, main objective of the questions manual is to enhance the student understanding on the subject matter of the Malaysian taxation. The questions manual aim to expose the students in applying the concepts and techniques learnt in the class. Due to that, the initiatives have been taken to compile all the relevant questions in accordance to the respective topics covered in the course.